2015
DOI: 10.1007/s10800-015-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-assisted electrochemical processes for the removal of persistent organic pollutants from wastewater

Abstract: This work focused on the removal of persistent organic pollutants (POPs) from wastewater using irradiation-assisted electrochemical technologies, i.e. sonoelectrolysis, photoelectrolysis and sono-photoelectrolysis. Single-irradiation processes (sonolysis and photolysis) and electrochemical oxidation using conductive diamond anodes (current density of 30 mA cm -2 ) were also evaluated for comparison. Three POPs with different molecular structures (sulfamethoxazole, metoprolol and caffeine, initial concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 45 publications
2
41
2
Order By: Relevance
“…In order to clarify this point, Figure 6 compares the synergistic effect (estimated according to equation 14) of the electro-irradiated treatment of AMX and AMP solutions and of other compounds previously studied in the literature [32,51] under similar operation conditions. In light of the obtained results, it can be said that although irradiation by UV light or US generates SO 4 and Cl species, and also promotes the formation of OH, this is not reflected in an improvement of the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…In order to clarify this point, Figure 6 compares the synergistic effect (estimated according to equation 14) of the electro-irradiated treatment of AMX and AMP solutions and of other compounds previously studied in the literature [32,51] under similar operation conditions. In light of the obtained results, it can be said that although irradiation by UV light or US generates SO 4 and Cl species, and also promotes the formation of OH, this is not reflected in an improvement of the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…Adewuyi and Khan (2012) provided a framework model for robust and rigorous development of sonochemical systems and reactors (Adewuyi and Khan 2012). Effective mineralisation of POPs, however, depends on the combination of ultrasonicator with other AOPs (de Vidales et al 2015).…”
Section: Cavitationmentioning
confidence: 99%
“…Active anodes such as mixed metal oxide (MMO) electrode showed low capability to directly degrade organic pollutants, while non‐active anodes such as boron‐doped diamond (BDD) exhibited higher ability to destroy recalcitrant contaminants due to its higher overpotential for oxygen evolution . Besides, common electrolytes including phosphate, chloride, and sulfate have been usually used to generate • OH, ozone, chlorine, ferrate, and other oxidants during electrochemical oxidation processes . In this study, MMO (IrO 2 /Ta 2 O 5 /Ti) electrodes were used to in situ generate the active chlorine in the presence of NaCl electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…–. The literature indicated that the combination of UV photolysis and single electrolysis oxidation can help promote the generation of hydroxyl radicals and the removal efficiency over the expected separate contributions . In this respect, UV photolysis can be used to expand the applicability of electrolysis processes and destroy the organic contaminants in water.…”
Section: Introductionmentioning
confidence: 99%